The Development of an Interactive Digital Book: Enhancing Elementary Students’ Critical Thinking Skills in Pancasila and Civic Education - Yussy Efita Salamor; Wuri Wuryandani (Journal of Educational Sciences, 2026)
Civic Education (PPKn) learning at the elementary school level continues to face several challenges, particularly the low level of students’ critical thinking skills.This study aims to develop an interactive digital book for Civic Education learning to enhance students’ critical thinking skills. The study employed a Research and Development (R&D) method using the ADDIE model. Product development involved validation by subject-matter experts and media experts, resulting in a material validation score of 93.75% and a media validation score of 93.83%. The product was subsequently tested in the field and analyzed through comparisons of pre-test and post-test results between the experimental and control groups. The use of printed textbooks and PowerPoint presentations in the control class resulted in a pre-test score of 43.88 (low category) and a post-test score of 78.75 (high category). In contrast, the use of the interactive digital book in the experimental class produced a pre-test score of 61.00 (moderate category) and a post-test score of 90.56 (very high category). The findings indicate that the interactive digital book met the criteria of being highly feasible. The practical implications of this study suggest that interactive digital books can serve as innovative instructional materials that promote more engaging and interactive.